Investigation of the effect of the onset of bruxism as a result of early antidepressant use - Güldiken, İpek; Elbir, Begüm; Nalimov, Andrei; Delilbaşı, Çağrı (My University, 2024)
Background: Among antidepressants, selective serotonin and noradrenaline reuptake inhibitors (SSRIs and SNRIs) have been widely used in the treatment of major depression and may induce sleep disorders and bruxism. In the present study, the effects of SSRIs and SNRIs on awake and sleep bruxism have been evaluated. Subjects and methods: A total of 125 patients who had been prescribed SSRIs or SNRIs for the treatment of major depression have been evaluated for bruxism. For the purpose of the study, data from the first week (T1) and the fourth week (T2) of antidepressant treatment have been considered. Results: In conclusion, in the early period, the presence of bruxism has not been observed to be significantly influenced by the use of antidepressants. It has been determined that sleep bruxism increased in the fourth week only in males who were using antidepressants (p = 0.015; p < 0.05). An increase in the presence of sleep bruxism due to specific SSRIs and SNRIs has been determined in the fourth week of drug use. Paroxetine in the SSRI group and duloxetine in the SNRI group have been found to cause an increase in sleep bruxism (p = 0.013; p < 0.05). Other active substances have not been found to affect sleep or awake bruxism significantly. Conclusion: The present study has shown that although some antidepressants increase bruxism in the early period of drug use, the effects of similar drugs on sleep or awake bruxism need to be evaluated in detail in long-term studies.
Keywords: Antidepressant; Bruxism; Depression; SNRI; SSRI